Developing and Defining Diversity. (4th May 2019) - Fisk, Jonathan M.; Silvera, Geoffrey A.; Haun, Courtney N.
Abstract: To gain and maintain legitimacy from internal and external stakeholders, public sector agencies and organizations have engaged in efforts to increase their diversity and cultural competency. While these changes are typically seen as welcomed, timely, and important, they also challenge organizations. To aid in diversity management scholarship and practice, this research develops a descriptive typology based on organizational outcomes and priorities and the degree to which the organization has institutionalized such programs.